Survei Tingkat Keterampilan Dribling, Passing dan Shooting dalam Permainan Futsal di Club Futsal Deco - Dzikri Chairuk As Sidiq; Firman Maulana; Muhammad Saleh (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the level of basic futsal technical skills, including dribbling, passing, and shooting, among players at the Deco Futsal Club in Sukabumi Regency. The background of this study is based on the importance of mastering basic techniques in determining game effectiveness and team achievement. Basic techniques such as dribbling, passing, and shooting are fundamental elements that influence the overall quality of the game. This study used a descriptive quantitative method with a survey approach through skills tests on 20 players. Each player was tested on their abilities in these three basic technical aspects and the results were analyzed to determine their respective skill level categories. The results showed that the majority of players were in the sufficient category for all three techniques tested. Among the three, passing skills showed relatively better results compared to dribbling and shooting. This finding indicates that although passing skills are quite good, there is a need to improve the quality of the players' dribbling and shooting. Based on these conditions, this study recommends the need for a more focused and structured basic technique training program. Coaches are expected to design training sessions that focus on improving speed and control in dribbling, accuracy in passing, and accuracy in shooting. The practical implication of this research is the need for regular evaluation of players' basic technical abilities to monitor skill development. Thus, it is hoped that the quality of play and the achievements of the Deco Futsal Club can be significantly improved by strengthening the technical aspects of individual players.